Research of temperature destruction effect on cables insulation operation life - V. N. Pugach; D. A. Polyakov; K. I. Nikitin; N. A. Tereshchenko; I. V. Komarov (Омский научный вестник)
Technological interruptions reduce in power supply companies is an important problem of electrical power engineering. The service life of power cables is one of the parameters that significantly affects the occurrence of breakdowns in cable insulation. The article describes the thermal aging of insulating materials of low-voltage cables and its effect on their service life. The wellknown mathematical models of insulation aging dependence on temperature are considered. Low-voltage cables are slightly affected by the electric field due to the large margin of electric strength. Therefore, it is assumed that such cables are being aged mainly due to their thermal operating conditions. Experimental studies of cable insulation temperature monitoring have been carried out. Seven weeks of the experiment show an insignificant temperature change. The article also evaluates the effect of insulation temperature on its service life. The results show a significant reduction in service life even with a slight increase in temperature, which shows a significant effect of thermal destruction of the insulating material.